Labeling male anorectal malformations: objective evaluation of radiologic imaging before surgery - Morandi, A.; Maestri, F.; Ichino, M.; Pavesi, M. A.; Macchini, F.; Di Cesare, A.; Leva, E. (Frontiers in Pediatrics, 2023)
Prone cross-table lateral x-ray (CTLxR) and colostogram aid surgical planning for anorectal malformation (ARM) without perineal fistula. We suggest objective imaging tools to classify ARMs.Methods: Three observers prospectively evaluated CTLxR and colostograms of male ARM patients (2012-2022) without perineal fistula. Rectal pouch level was estimated with pubococcygeal (PC) and ischiatic (I) lines. We described the "pigeon sign" on CTLxR: a beak-like image, suspicious for rectourinary fistula. ARM was defined: rectobulbar with rectal pouch below I line, rectoprostatic between PC and I lines, and rectovesical above PC line. Concordance was assessed with Fleiss' kappa. Sensitivity, specificity, positive predictive (PPV) and negative predictive values (NPV) for "pigeon sign" were calculated.Results: Thirteen patients were included. Interobserver agreement on CTLxRs was: 69.2% (k=0.54) on pouch ending, 84.6% (k=0.69) on "pigeon sign", and 76.9% (k=0.69) on diagnosis; concordance between observers and intraoperative diagnosis was 66.6% (k=0.56). "Pigeon sign" had 75% sensitivity, 100% specificity, 100% PPV, 50% NPV.Interobserver agreement on colostograms was: 84.6% (k=0.77) on pouch ending, 89.7% (k=0.86) on diagnosis; concordance among observers and intraoperative diagnosis was 92.3% (k=0.90).PC and I lines, and "pigeon sign" are useful tools in examining CTLxRs and colostograms. Adequate CTLxR interpretation may modify surgical strategy.